2020
DOI: 10.1111/jocd.13614
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A as a novel method of preventing cleft lip scar hypertrophy—A literature review

Abstract: BackgroundCleft lip is a congenital development defect. Primary cleft lip repair leads to cleft scar formation. The resulting scar often undergoes hypertrophy, which negatively affects the facial esthetics, function, and patient's mental health. One of the methods used in scar therapy described in recent years is botulinum toxin injections The aim of this work is to present current knowledge about the impact of botulinum toxin A on cleft lip scar appearance and its effect on scar hypertrophy.MethodsThe literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
7
0
6
Order By: Relevance
“…Botulinum toxin, released from Clostridium botulinum bacteria, is a neurotoxin that inhibits neuromuscular transmission indirectly. In spite of the presence of many types of botulinum toxin (A–F), botulinum toxin type A has been used extensively to improve facial wrinkles 19 . Moreover, it is known to minimize scarring and prevent skin contractions during healing by altering fibroblast signalling pathways 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botulinum toxin, released from Clostridium botulinum bacteria, is a neurotoxin that inhibits neuromuscular transmission indirectly. In spite of the presence of many types of botulinum toxin (A–F), botulinum toxin type A has been used extensively to improve facial wrinkles 19 . Moreover, it is known to minimize scarring and prevent skin contractions during healing by altering fibroblast signalling pathways 15 …”
Section: Introductionmentioning
confidence: 99%
“…In spite of the presence of many types of botulinum toxin (A-F), botulinum toxin type A has been used extensively to improve facial wrinkles. 19 Moreover, it is known to minimize scarring and prevent skin contractions during healing by altering fibroblast signalling pathways. 15 Folic acid (vitamin B9) participates in DNA synthesis and repair.…”
mentioning
confidence: 99%
“…A more expansive review of the literature 2 years prior by Bartkowska et al [31] looked at various studies showing unanimous improvements in VAS, VSS, and scar width measurements in the Botox-A administered study groups with no reported complications. Another factor leading to the formation of hypertrophic scars is the expression of transforming growth factor-β1 (TGF-β1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 causes proliferation of human fibroblasts, and ultimately the production of collagens I and III. Botox-A has been shown not only to downregulate TGF-β1, but also to promote the apoptosis of well differentiated fibroblasts [30,31]. One thing to note is that the dose of the toxin and the timing of the injections (before, during, or after surgery) differed between the studies examined [31].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous studies have suggested that BTXA may be effective in suppressing scars in various parts of the body. In a recent review, Bartkowska et al 14 concluded that injecting BTXA appears to be a promising method in cleft lip scar management. However, this review lacks statistical data support.…”
Section: Introductionmentioning
confidence: 99%